2014
DOI: 10.1111/jvim.12334
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Serum Spec cPL with the 1,2‐o‐Dilauryl‐Rac‐Glycero Glutaric Acid‐(6′‐methylresorufin) Ester (DGGR) Lipase Assay and with Pancreatic Ultrasonography in Dogs with Suspected Pancreatitis

Abstract: BackgroundSpec cPL is the most sensitive and specific test for diagnosing pancreatitis in dogs. Its results have not been compared to those of the 1,2‐o‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester (DGGR) lipase assay or those of abdominal ultrasonography.ObjectivesTo investigate agreement of Spec cPL with DGGR lipase activity and pancreatic ultrasonography in dogs with suspected pancreatitis.AnimalsOne hundred and forty‐two dogs.Methods DGGR lipase activity (reference range, 24–108 U/L) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 27 publications
9
89
0
1
Order By: Relevance
“…Our study found only fair agreement between AUS and PLI for the diagnosis of pancreatic injury ( κ = 0.26). This agrees with the findings of a recent study, where despite excellent agreement between two lipase assays for pancreatic injury (DGGR lipase assay and PLI, κ = 0.80), only fair agreement ( κ = 0.25) was found between both lipase assays and AUS . There are several potential explanations for limited agreement between AUS and PLI in our study population.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found only fair agreement between AUS and PLI for the diagnosis of pancreatic injury ( κ = 0.26). This agrees with the findings of a recent study, where despite excellent agreement between two lipase assays for pancreatic injury (DGGR lipase assay and PLI, κ = 0.80), only fair agreement ( κ = 0.25) was found between both lipase assays and AUS . There are several potential explanations for limited agreement between AUS and PLI in our study population.…”
Section: Discussionsupporting
confidence: 91%
“…In this retrospective study, we evaluated the correlation between ultrasonographic evidence of pancreatitis, pancreatic lipase concentration, clinical severity indices, and a CDx of pancreatitis in 157 client‐owned dogs. The results of this study highlight a discrepancy between AUS and pancreatic lipase concentrations in the diagnosis of pancreatitis in dogs, similar to previously reported . This study also highlights a discrepancy between the ultrasonographic assessment of severity of pancreatitis and the validated clinical severity indices with only minor modifications.…”
Section: Discussionsupporting
confidence: 80%
“…However, concentrations of canine pancreas‐specific lipase by quantitative ELISA test (Spec cPL test, Idexx Laboratories) are increased in dogs with HAC without clinical evidence of pancreatitis compared to healthy dogs . A good agreement and strong correlation has been shown between lipase activity measured by the DGGR assay and the Spec cPL test in several studies, and thus finding increased lipase activity in dogs with HAC in our study was not unexpected. Whether HAC is a predisposing factor for pancreatitis remains unresolved.…”
Section: Discussionsupporting
confidence: 80%